2021
DOI: 10.1371/journal.pone.0257053
|View full text |Cite
|
Sign up to set email alerts
|

Soil fertility interactions with Sinorhizobium-legume symbiosis in a simulated Martian regolith; effects on nitrogen content and plant health

Abstract: Due to increasing population growth and declining arable land on Earth, astroagriculture will be vital to terraform Martian regolith for settlement. Nodulating plants and their N-fixing symbionts may play a role in increasing Martian soil fertility. On Earth, clover (Melilotus officinalis) forms a symbiotic relationship with the N-fixing bacteria Sinorhizobium meliloti; clover has been previously grown in simulated regolith yet without bacterial inoculation. In this study, we inoculated clover with S. meliloti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…A study involving legume-Rhizobia symbiosis in Mars regolith simulants showed more nodulation in the MMS-2 regolith simulant compared to MMS-1, where MMS-2 contains added compounds such as Iron Oxide, Magnesium Oxide, Sulfates and Silicates [ 64 ]. Another similar study on legume-Rhizobia interactions in MMS-1 suggested that the high pH of the regolith may impair Fe uptake by the plants, Fe being a key factor for plants to sustain a healthy relationship with rhizobia, which would in turn negatively impact nodulation [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study involving legume-Rhizobia symbiosis in Mars regolith simulants showed more nodulation in the MMS-2 regolith simulant compared to MMS-1, where MMS-2 contains added compounds such as Iron Oxide, Magnesium Oxide, Sulfates and Silicates [ 64 ]. Another similar study on legume-Rhizobia interactions in MMS-1 suggested that the high pH of the regolith may impair Fe uptake by the plants, Fe being a key factor for plants to sustain a healthy relationship with rhizobia, which would in turn negatively impact nodulation [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased Martian soil fertility through symbiotic relationships has been examined with clover ( Melilotus officinalis ), grown in simulated regolith that had been inoculated with the nitrogen-fixing bacterium, Sinorhizobium meliloti 56 . This study found that after three months, inoculated treatments produced greater clover biomass compared to uninoculated treatments, 0.29 g and 0.01 g, respectively.…”
Section: Bioregenerative Life Support Systems and The Value Of Microb...mentioning
confidence: 99%
“…In addition, many educational institutions use Mars simulant soils for demonstrations on Martian geology and extraterrestrial agriculture [13][14][15]. Furthermore, recent research demonstrates that microorganisms can effectively enhance soil nutrients available and facilitate crop growth in Mars simulant soil [16][17][18]. This highlights the importance of obtaining soil DNA to understand the interaction between microorganisms and Mars simulant soils, and to perform subsequent sequencing analysis of microbial functions.…”
Section: Introductionmentioning
confidence: 99%